Research on certain aspects of PR function in Serbian - Milan Nikolic; Dejan Djordjevic; Dragan Cockalo (Journal for East European Management Studies, 2007)
The paper presents the results of the research on certain aspects of PR function in Serbian companies. 70 PR managers were polled, and it is estimated that they represent a third of the total number of PR managers in Serbia. 29 questions were asked, and they were divided into three characteristic categories: a) Questions relevant to the analysis of the position of PR managers and their profession; b) Questions relevant to the analysis of characteristic profession and education of PR managers; c) Questions relevant to the analysis of the most frequent and most important activities and media for the performance of PR function. In addition to the presentation of the results of the survey, the paper also presents their detailed analysis. – – Der Aufsatz präsentiert die Resultate der Untersuchung bestimmter Aspekte der PR Funktion in serbischen Unternehmen. 70 PR Manager wurden befragt, die voraussichtlich ein Drittel der PR Manager Serbiens repräsentieren. Es gab 29 Fragen zu beantworten, die sich auf drei charakteristische Kategorien verteilten: a) Fragen im Hinblick auf die Analyse der Positionen der PR Manager und deren Ausübung; b) Fragen im Hinblick auf die Analyse des typischen Berufs und der Ausbildung der PR Manager; c) Fragen im Hinblick auf die Analyse der meist verwendeten und wichtigsten Maßnahmen und Hilftsmittel bei der Ausführung der PR Funktion. Neben der Präsentation der Umfrageergebnisse legt der Artikel auch eine detaillierte Analyse vor.
Keywords: 650; Communication; PR managers; research; results; analyses; Serbia